Strengthening District Administration in Plural Communal Context: An Analysis on the Potential Impact of Establishing a Kalmunai Administrative District in Sri Lanka - Yusoff, Moharnrnad Agus (Atlantis Press SARL, 2018)
Decentralization promotes and strengthens the quality of local administration in plural communal context. However, decentralized district administration in postindependence Sri Lanka has been challenging, primarily due to a number of issues related to the accommodation of rights and interests of minorities. The persistent sidetracking of minorities’ concerns in district administration has pushed them to claim and advocate for separate decentralized institutional arrangements. One such issue is the call to form a separate administrative district (referred to as “Kalmunai administrative district”) in the coastal belt of the existing Amparai district. While exploring the factors that motivated the concept of a new administrative district, this study examined the potential impact of the formation of a Kalmunai administrative district. This research employed qualitative and quantitative data collected through different sources, which are presented through interpretive and descriptive arguments. The findings reveal that the conceptualization and advocacy of the Kalmunai administrative district are outcomes of several interconnected factors that undermined the rights and interests of ethnolinguistic minorities in decentralized district administration. These factors include the administrative domination of the ethnic majority, violation of the official language policy, and discrimination and marginalization of ethnic minorities in the district administration affairs. However, this study suggests that the establishment of the proposed administrative district would not only improve the quality of public service delivery and accommodate linguistic concerns of minorities in the district administration but would also enhance the socioeconomic development in the region, if the district administration is carefully organized and managed